An??lise da coexist??ncia do 5G NR com comunica????es terrestres e satelitais - Alexandre, Luciano Camilo (2020)
This work reports experimental coexistence analyses of the fifth generation of mobile network (5G) new standard named as 5G New Radio (5G NR), with terrestrial and satellite wireless communications in the 700 MHz- and C-bands, respectively. Initially, performance results of the coexistence between 5G and the fourth generation of mobile network (4G) are presented, using Long Term Evolution Advanced Pro (LTE-A Pro) and Narrow Band Internet of Things (NB-IoT) technologies, under adjacent channel and co-channel conditions in the 700 MHz band. The second phase concerns the coexistence between 5G NR and TVRO (Television Receive Only) systems in the 3.5 GHz band, operating from 3625 to 4200 MHz. The evaluated performance metrics were error vector magnitude (EVM) for the experiments between 5G and 4G and image quality of the analog and digital channels of TVRO system in the presence of the interfering 5G signal. Experimental results demonstrate a peaceful coexistence between 5G and 4G for frequency offsets greater than 9.4 MHz and even for co-channel conditions, by means of using the 5G NR CORESET feature. On the other hand, it is proven 5G systems operating in the 3.5 GHz band might significantly degrade the quality of analog and digital channels for distances lower than 120 meters. Aiming to mitigate this problem, which might reach approximately 22 million Brazilian households, according to the national household sample survey, adaptations on the LNBF (Low Noise Block Feeder) blocks of the current satellite dishes are proposed, as well as the development of high performance and low-cost RF filter, capable of rejecting up to 59 dB of the interfering 5G signal. The proposed adaptations on the 1dB compression point of the LNBF and the proposed RF filter applicability are analytically validated, using ITU (International Telecommunication Union) recommendation. In this way, it is proved a TVRO system protection distance significant reduction from 30.2kilometers to 133 meters.